Feeding calf starter: growth performance of crossbred dairy calves (Asian-Australasian Journal of Bioscience and Biotechnology, 2024)
Calf starter is a special feed preparation that is fed to calves to ensure smooth weaning of calves. The study was conducted to evaluate the growth performance of crossbred dairy calves (Holstein-Friesian crossbred, HFX and Sahiwal crossbred, ShX) feeding a readily fermentable calf starter diet. The duration of the study was 17 weeks of which the first week was for the adjustment period. Ten healthy crossbred heifer calves of average 40 days old were selected for this purpose and they were divided into two groups according to their genetic materials (5 HFX and 5 ShX) in a completely randomized design. The calves were fed initially 0.25kg/day/calf of starter feed which was gradually increased up to 1 kg/day/calf. In addition to calf starter, a predetermined amount of whole milk (2 kg/day/calf) and ad libitum amount of green grass were also supplied to the calves. During the experimental period, growth parameters viz. body weight gain, body length gain, wither height gain, and hip height gain was measured weekly. After the whole study period, no significant difference (P>0.05) was found in case of the average weekly body weight gain and all the body measurements. The results suggest that calves fed a balanced calf starter can grow identically overcoming any breed variations. However, to provide a clearer idea about the effect of calf starter on different crossbred dairy calves broad-scale research should be conducted on an advanced level including more crossbreds or pure breeds.Asian Australas. J. Biosci. Biotechnol. 2024, 9(1), 4-9